SOSIALISASI UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK (ITE) DALAM PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA USAHA - lenny Husna; Yusli Yenni (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2020)
Nowadays almost all aspects of life use technology. Progress in technology will also be accompanied by developments in information and communication technology. The development of technology and communication using internet media that is widely used today is social media. Some people use social media for means of social integration, communication and publicizing activities, but in its development social media can also be used for business activities in terms of promotion and marketing. The use of social media for business activities has a very positive impact on improving the welfare of the community economically. To achieve these objectives, training and coaching to the public regarding the use of social media are held. The training was carried out at the Pesona Rhabayu Housing Community of Patam Lestari Village, Sekupang District, Batam. The training was conducted by monitoring and tutorials on how to use social media properly, including information dissemination on the Information and Electronic Transaction Law (UU ITE) so that the community has a legal basis for using social media. The first result of this dedication is that people's understanding of the ITE Law can be seen from discussions and questions and answers, secondly, people's ability to access and utilize social media for business facilities by forming a social media group as a forum for the community to promote their efforts.Keywords: Law, social media and ITE